Respuesta en frecuencia de la pared arterial: ¿inocente o culpable de las discrepancias entre filtrado sistémico y pulmonar? - Armentano, Ricardo L.; Bia, Daniel; Craiem, Damián; Gamero, Lucas; Levenson, Jaime; Grignola, Juan C.; Ginés, Fernando F. (Revista Mexicana de Ingenieria Biomedica, 2003)
Objective: To characterize the mechanical properties of the Aorta (AO) and the pulmonary (PA) arteries and the effect of the vascular smooth muscle activation (VSM). Method: Aortic and pulmonary pressures (Konigsberg) and diameters (sonomicrometry) were measured in 6 anaesthetized sheep. A Kelvin-Voigt model, with non-negligible mass was used to characterized the wall mechanical properties and identified by means of a linear auto-regressive model with exogenous input. Elasticity (E), viscosity (η) and inertial (M) indexes were calculated during control state and VSM activation (Phenylephrine, PHE 5 µg/kg/min). The frequency response of the arterial system was estimated by the natural frequency and buffering factor. The diastolic time constant was calculated as a global buffering function index (two-element Windkessel model). Results: Both arteries showed a low-pass filter response. The AO showed a higher E, η and M, however dissipation (η) /energy-storage (E) was similar in both arteries and in both experimental conditions. The dynamic range was similar for both arteries and with no change during PHE. The whole system buffering function was higher in the systemic circuit with respect to the pulmonary, and did not modify during activation. Conclusion: The enhanced attenuation revealed by the systemic circuit could be regarded to its longer effective length in respect with the pulmonary path. The sustained administration of PHE, by means of the local smooth muscle activation, exerts a beneficial effect for the circulation, preserving the wall dynamic range making more sensible the viscosity and less sensible the elasticity under pressure rises.